Pectin Extraction from Various Sources: A Literature Review - Triyatna, Vira; Fetriyuna, Fetriyuna; Rohmah, Miftakhur (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
Plant cell walls include a complex polymer called pectin, which combines methoxyl with galacturonic acid to produce a gel. Applications for pectin are found in both the food and non-food industries. It is utilized as an edible coating, gel-forming, texture enhancer, stability enhancer, and appearance enhancer in the food industry. Pectin can be combined with other ingredients to make non-food products. For example, pectin, chitosan, carboxymethyl cellulose (CMC), and alginate can be used to make biocomposites for wound dressings. Other sources of pectin include aloe vera, biosorbent, banana peel, corn starch, albedo watermelon, nutmeg, pumpkin, and dragon fruit skin. The properties of pectin are generally determined by its yield, equivalent weight, methoxyl content, galacturonic acid content, and degree of esterification. The two most common methods used to extract pectin are chemical and mechanical. Typically, chemical processes use solvents and mechanical techniques to combine liquid and solid components.